Loneliness, social provision and health among older men and women with chronic physical diseases - a mixed methods study - Heidi Bjørge; Børge Baklien; Elin Opheim; Kari Sofie Kvaal; Knut Ragnvald Skulberg (Taylor & Francis Group, 2024)
AbstractThe purpose of the study was to explore loneliness, social provision and perceived health from a gender perspective among older persons with chronic diseases. Loneliness has become one of the main challenges facing an ageing society. It is not only a health concern, but also involves social, cultural and relational issues. A mixed-methods approach was chosen to enable a deeper insight into the participants' experience of loneliness. Perceived social support was assessed by the Social Provisions Scale and self-rated health was reported by 42 older participants with chronic diseases. An interview was conducted with 27 participants who reported feeling lonely. Analysis revealed no gender differences in the survey of social provision, but the association between social provision and self-rated health was much stronger in women than compared to men. In their statements, the female participants expressed missing emotional support, someone to talk to and relationships with their family. The male participants longed for contact and wanted help to get out of the house. Their need for relief strategies against loneliness seems to be closely linked to their previous traditional gender roles. The results indicate that society could improve the health of older persons by promoting safe social contacts, preferably in smaller interest groups, as well as facilitating social contact in society, e.g. social meeting places.